MODERASI KOMITMEN ORGANISASI TERHADAP HUBUNGAN ANTARA PARTISIPASI ANGGARAN DENGAN KINERJA MANAJERIAL DI KABUPATEN HALMAHERA BARAT - Djaelani, Yustiana; Subhan, Subhan (Jurnal Akun Nabelo : Jurnal Akuntansi Netral, Akuntabel, Objektif, 2019)
This study examines the effect of budgetary participation on managerial performance with organizational commitment as a moderating variable. The purpose of the study was to find empirical evidences about the relationship and positive and significant influence between budgetary participation and managerial performance, and organizational commitment can be a moderation of the relationship between budgetary participation and managerial performance. The study respondents were budget compilers in SKPD in West Halmahera Regency, with a sample of 64 respondents. Data collection with a list of questions adopted from previous researchers. The collected data is processed using moderating regression analysis (MRA) and regression interactions between variables. The results of the study are (1) there is a significant influence and positive relationship between budgetary participation and managerial performance; and (2) there is no influence of organizational commitment on the relationship of budgetary participation and managerial performance.